Effects of wild rose (Rosa sp.) crude seed extracts on two legume aphids - Zohra, Ben Cheikh-Affene; Ikbal, Chaieb; Faouzi, Haouala; Fethia, Harzallah-Skhiri (Pharmacognosy Communications)
Crude hexane seed extracts of four wild species of roses of Caninae Section: Rosa canina L., Rosa dumetorum Thuiller., Rosa pomifera Herm. and Rosa rubiginosa L., from Kairouan and Beja regions, were screened for their insecticidal activity on two aphid species: black bean aphid (Aphis fabae Scop.) and pea aphid (Acyrthosiphon pisum Scop.) which feed on several cultivated species. The composition of hexane seed extracts permitted the identification of fifteen compounds. R. dumetorum was richeest in palmitic acid (7.1%), stearic acid (2.6%), oleic acid (22.2%). R. ruboginosa (Kairouan region) was richer in linoleic acid (52.8%) whilst R. pomifera was higher in linolenic acid (26.9%).Tests were conducted using in vitro spraying of each rose seed extract at four doses: 0, 10, 20 and 40 mg ml–1. Results showed a greater sensitivity of Aphis fabae to the rose extracts. Indeed, at the dose of 40 mg ml–1, the mortality varied from 25 to 47% for Aphis fabae and from 22 to 34% for Acyrthosiphon pisum. The maximum ofmortality for the two aphid species was observed with the hexane extracts of R. dumetorum. This insecticidal activity may be due to the presence of arachidic acid in the tested extracts.
Keywords: Acyrthosiphon pisum; Aphis fabae; fatty acids; insecticidal activity; Rosa canina; Rosa dumetorum; Rosa pomifera; Rosa rubiginosa